Low-temperature impact resistant transparent chemical resistant pc / pctg alloy and preparation method and application thereof
Patent Information
- Application Number
- CN202510613524.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-05-13
AI Technical Summary
然而,传统PC材料在长期使用中逐渐暴露出若干关键性缺陷:首先,其耐化学性较差,易受有机溶剂、油脂等介质的侵蚀,导致应力开裂风险显著上升;其次,低温环境下(如-30℃以下)冲击韧性急剧下降,限制了其在寒冷地区或低温工况下的应用;此外,高粘度导致的加工流动性不足,也制约了复杂结构制件的成型效率
[0024]本发明提供的耐低温冲击透明耐化学性PC/PCTG合金,以双酚A型PC树脂和硅共聚PC树脂共同作为PC树脂,其中,硅氧烷链段可以赋予材料高柔顺性,在受到冲击时通过微相分离结构吸收能量,显著提高低温抗冲性(-30℃以下仍保持韧性),避免传统PC的低温脆裂问题。通过调配耐低温冲击透明耐化学性PC/PCTG合金的制备原料的组合和配比,有利于制备得到兼具高透明、高冲击、高流动、耐化学性能的PC/PCTG合金产品,不仅可用于玻璃装配业、电动工具、清洁家电、汽车工业、电子电器、机械零部件、光盘、包装、计算机等办公室设备、医疗及保健、薄膜、休闲和防护器材等领域,还可用于需要耐化学性、透明、一定高度抗跌落、一定的耐热条件环境中,如用于扫地机器人、蒸汽拖把、洗地机、电动工具外壳等应用方面。
Smart Images

Figure CN120310210B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and more specifically, to a low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy, its preparation method, and its applications. Background Technology
[0002] Polycarbonate (PC), as a thermoplastic engineering plastic with excellent comprehensive performance, is widely used in automotive parts, electronics, medical devices, and other fields due to its high transparency, excellent impact resistance, heat resistance, and dimensional stability. However, traditional PC materials have gradually revealed several key defects in long-term use: First, its chemical resistance is poor, making it susceptible to corrosion from organic solvents, oils, and other media, leading to a significant increase in the risk of stress cracking; second, its impact toughness decreases sharply at low temperatures (such as below -30°C), limiting its application in cold regions or low-temperature conditions; in addition, its high viscosity results in insufficient processing fluidity, which also restricts the molding efficiency of complex structural parts.
[0003] To address the performance shortcomings of PC, the industry often employs a blending modification approach. For example, blending with PBT can improve chemical resistance but leads to a loss of transparency in the alloy; blending with PMMA maintains transparency but sacrifices impact strength. In recent years, copolyester materials such as PCTG have attracted attention due to their excellent chemical corrosion resistance, high light transmittance, and low-temperature toughness. However, pure PCTG has low mechanical strength and low heat resistance, making it difficult to meet the requirements of structural components when used alone. Therefore, developing a low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy is considered a potential solution, but this system faces two major technical bottlenecks: firstly, PC and PCTG have poor compatibility, and simple blending easily leads to phase separation, resulting in increased haze and decreased mechanical properties; secondly, during high-temperature processing, the two are prone to transesterification reactions, which disrupt the molecular chain regularity, causing a decrease in transparency, mechanical properties, and thermal stability.
[0004] With the rapid development of emerging fields such as new energy vehicles, clean home appliances, outdoor optical equipment, and cryogenic medical devices, the market demand for multifunctional materials that combine high transparency, low-temperature impact resistance, chemical resistance, and ease of processing is becoming increasingly urgent. Therefore, developing a PC-based alloy material that achieves a performance balance through precise component design while maintaining process feasibility has become an important research direction in the field of polymer composite materials.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a low-temperature impact resistant, transparent, and chemically resistant PC / PCTG alloy, its preparation method, and its application, thereby improving the market demand for multifunctional materials with high transparency, low-temperature impact resistance, and chemical resistance.
[0007] This invention is implemented as follows:
[0008] In a first aspect, the present invention provides a low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy. By weight percentage, the raw materials for preparing the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy include: 10-30% bisphenol A type PC resin, 16-30% silicone copolymer PC resin, 36-65% PCTG resin, 1-3% toughening agent, 0.3-0.5% antioxidant, 0.2-0.5% lubricant, and 0.1-0.5% transesterification inhibitor.
[0009] In an optional embodiment, the mass ratio of the bisphenol A type PC resin to the PCTG resin is 1:1.35-2.
[0010] In an optional embodiment, the mass ratio of the bisphenol A type PC resin to the silicone copolymer PC resin is 1:0.59-1.25.
[0011] In an optional embodiment, the bisphenol A type PC resin is a transparent bisphenol A type polycarbonate with a light transmittance of ≥89%.
[0012] In an optional embodiment, the siloxane content of the silicone copolymer PC resin is at least 6%, 8%, and 20%.
[0013] In an optional embodiment, the raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, by weight percentage, include: 20-27% bisphenol A type PC resin, 16-25% silicone copolymer PC resin, 36-65% PCTG resin, 1-2% toughening agent, 0.3-0.4% antioxidant, 0.2-0.4% lubricant, and 0.2-0.4% transesterification inhibitor.
[0014] In an optional embodiment, the PCTG resin is a polyethylene terephthalate-1,4-cyclohexanediol resin with a viscosity of 1.00 to 1.05 l / g.
[0015] And / or, the toughening agent comprises at least one of methyl methacrylate-butadiene-styrene copolymer, ethylene-methyl methacrylate-glycidyl methacrylate terpolymer, butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer, ethylene-butyl methacrylate-glycidyl methacrylate copolymer, and methyl methacrylate-styrene-silicone-butyl acrylate.
[0016] And / or, the antioxidant comprises at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide), tris[2,4-di-tert-butylphenyl] phosphite, oxaloyl(diimino-2,1-ethylidene)propionate (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and bis(2,4-dicumylphenyl)pentaerythritol diphosphite;
[0017] And / or, the lubricant includes at least one of polyethylene wax, OP wax, PETS and montana wax;
[0018] And / or, the transesterification inhibitor includes at least one of sodium dihydrogen phosphate, zinc dihydrogen phosphate, sodium pyrophosphate, sodium metaphosphate, tetraethyl orthosilicate, triethyl phosphite, triphenyl phosphite, diisooctyl phosphate, and alkyl phosphates.
[0019] In a second aspect, the present invention provides a method for preparing a low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy, which includes extruding, cooling, granulating, drying, and injection molding the raw materials for preparing the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy as described in any of the foregoing embodiments.
[0020] Preferably, the extrusion is performed using a twin-screw extruder with a length-to-diameter ratio (L / D) of 32 to 44:1.
[0021] In an optional embodiment, the twin-screw extruder has 10 temperature zones, the temperatures of which are sequentially 100℃~120℃, 220℃~230℃, 230℃~230℃, 230℃~240℃, 230℃~240℃, 230℃~240℃, 230℃~240℃, 230℃~240℃, and 230℃~240℃, and the rotational speed of the twin-screw extruder is 200rpm~300rpm.
[0022] Thirdly, the present invention provides the application of the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy as described in any of the foregoing embodiments in the manufacture of office equipment, medical devices, health care equipment, protective equipment, or household appliances.
[0023] The present invention has the following beneficial effects:
[0024] The low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy provided by this invention uses bisphenol A type PC resin and silicone copolymer PC resin as the PC resin. The siloxane segments impart high flexibility to the material, absorbing energy through a microphase separation structure upon impact, significantly improving low-temperature impact resistance (maintaining toughness even below -30℃), thus avoiding the low-temperature brittleness problem of traditional PC. By adjusting the combination and ratio of raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, it is beneficial to prepare PC / PCTG alloy products with high transparency, high impact resistance, high flowability, and chemical resistance. These products can be used not only in the glass assembly industry, power tools, cleaning appliances, automotive industry, electronics, mechanical parts, optical discs, packaging, office equipment such as computers, medical and healthcare products, films, leisure and protective equipment, but also in environments requiring chemical resistance, transparency, a certain degree of drop resistance, and certain heat resistance, such as in applications like robotic vacuum cleaners, steam mops, floor scrubbers, and power tool housings. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 The screw combination used in the twin-screw extruder during extrusion in Embodiment 1 of this application;
[0027] Figure 2 The screw combination used in the twin-screw extruder during extrusion in Comparative Example 12 of this application;
[0028] Figure 3 The screw combination used in the twin-screw extruder during extrusion is shown in Comparative Example 13 of this application. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0030] This invention provides a low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy. The raw materials for preparing this low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, by weight percentage, include: 10-30% bisphenol A type PC resin, 16-30% silicone copolymer PC resin, 36-65% PCTG resin, 1-3% toughening agent, 0.3-0.5% antioxidant, 0.2-0.5% lubricant, and 0.1-0.5% transesterification inhibitor.
[0031] In this invention, bisphenol A type PC resin and silicone copolymer PC resin are used together as the PC resin. The bisphenol A type PC provides a rigid framework, while the dispersed phase of the silicone copolymer PC forms an "island structure," inducing crazes and shear bands, thus preventing crack propagation. The siloxane segments impart high flexibility to the material, absorbing energy through the microphase separation structure upon impact, significantly improving low-temperature impact resistance (maintaining toughness even below -30°C), avoiding the low-temperature brittleness problem of traditional PC. The silicon bond (Si-O) bond energy is higher than the C-C bond, resulting in stronger resistance to UV degradation and extending the outdoor service life of the composite material (e.g., automotive headlight covers, photovoltaic modules). It also helps reduce the photo-oxidation of bisphenol A groups; the silicone copolymer can shield some UV rays, delaying the yellowing and embrittlement of the PC backbone. The siloxane segments reduce melt viscosity, making the composite resin easier to mold (suitable for thin-walled products or complex structures), while also reducing energy consumption during injection molding.
[0032] Specifically, in this invention, the bisphenol A type PC resin is a transparent bisphenol A type polycarbonate with a light transmittance ≥89%. The amount of bisphenol A type PC resin can be any value among 10%, 15%, 20%, 25%, 30%, etc., or any range between two values.
[0033] Excessive silicon content in silicone copolymer PC resin can lead to phase separation, resulting in decreased transparency. In this application, the siloxane content of the silicone copolymer PC resin is limited to at least one of 6%, 8%, and 20%, which allows for control of the siloxane content to prevent excessive silicon content. The amount of silicone copolymer PC resin used can be any value from 16%, 18%, 20%, 25%, 30%, or any range between two values.
[0034] Furthermore, in this invention, the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin is 1:0.59-1.25. It can be seen that the compounding of the two improves compatibility and maintains better strength. Exemplarily, the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin can be any value from 1:0.59, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.25, or any range between the two.
[0035] In some embodiments, the PC can be, for example, a transparent bisphenol A polycarbonate with a light transmittance of ≥89%, or a silicon copolymer PC containing 6% siloxane, thereby enabling the alloy product to have good light transmittance.
[0036] In some embodiments, the PCTG resin is a polyethylene terephthalate-1,4-cyclohexanediol resin with a viscosity of 1.00–1.05 L / g. PCTG possesses high transparency, high impact strength, and excellent chemical resistance; however, its poor heat resistance limits its use in environments requiring heat resistance (e.g., 100°C). This invention blends PC and PCTG under the aforementioned conditions, enabling the PC / PCTG alloy to maintain high impact performance without affecting transparency. Furthermore, it improves the chemical resistance and processability of the product while meeting certain heat resistance requirements (e.g., 100°C).
[0037] Optionally, the mass ratio of bisphenol A type PC resin to PCTG resin is 1:1.35-2. Exemplarily, the mass ratio of bisphenol A type PC resin to PCTG resin is any one of 1:1.35, 1:1.4, 1:1.5, 1:1.7, 1:1.9, 1:2, or a range between any two. In some more typical embodiments, the mass ratio of bisphenol A type PC to PCTG is 1:1.9.
[0038] In an optional embodiment, the raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, by weight percentage, include: 20-27% bisphenol A type PC resin, 16-25% silicone copolymer PC resin, 36-65% PCTG resin, 1-2% toughening agent, 0.3-0.4% antioxidant, 0.2-0.4% lubricant, and 0.2-0.4% transesterification inhibitor.
[0039] In this invention, the toughening agent may, by way of example but not by way of limitation, include at least one of the following: methyl methacrylate-butadiene-styrene copolymer (MBS), ethylene-methyl methacrylate-glycidyl methacrylate terpolymer, ethylene-acrylic plastic (EAA), butadiene-styrene copolymer, ethylene-butyl methacrylate-glycidyl methacrylate copolymer (PTW), glycidyl methacrylate (GMA), styrene-butadiene thermoplastic elastomer (SBS), and methyl methacrylate-styrene-silicone-butyl acrylate.
[0040] In some typical embodiments, the toughening agent includes methyl methacrylate-butadiene-styrene copolymer (MBS) and ethylene-methyl acrylate-glycidyl methacrylate terpolymer. The mass ratio of the methyl methacrylate-butadiene-styrene copolymer to the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is from 1.1:1 to 2.5:1, such as 1:1, 2:1, or 2.5:1, or other values within the range of 1:1 to 2.5:1, preferably 1:1.
[0041] The MBS used in the aforementioned toughening agent has a refractive index close to that of PC and PCTG, hardly affecting the transparency of the PC / PCTG alloy. Furthermore, the MBS particle size is less than 100 μm, allowing for uniform distribution within the alloy material, which is beneficial for improving its impact strength. The ethylene-methyl acrylate-glycidyl methacrylate used in the aforementioned toughening agent exhibits high reactivity, increasing the compatibility of PC and PCTG and further enhancing the impact strength of the alloy product. Blending methyl methacrylate-butadiene-styrene copolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer in the aforementioned proportions is beneficial for achieving better overall performance in the alloy product.
[0042] In this invention, antioxidants may, by way of example but not by way of limitation, include at least one of the following: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (abbreviated as antioxidant 1010), N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (abbreviated as antioxidant 1098), tris[2,4-di-tert-butylphenyl] phosphite (abbreviated as antioxidant 168), oxaloyl(diimino-2,1-ethylidene)propionate (abbreviated as antioxidant 697), and bis(2,4-dicumylphenyl) pentaerythritol diphosphite (abbreviated as antioxidant 608), preferably including at least two of the above substances.
[0043] In some typical embodiments, the antioxidants include antioxidant 1010 and antioxidant 608. The mass ratio of antioxidant 1010 to antioxidant 608 can be from 1:1 to 1:2.5, such as 1:1, 1:2 or 1:2.5, preferably 1:1.
[0044] In this invention, the lubricant may, by way of example but not by way of limitation, include at least one of polyethylene wax, OP wax, PETS, and montana wax.
[0045] In some typical implementations, the lubricant includes PETS.
[0046] In this invention, the transesterification inhibitor may, by way of example but not by way of limitation, include at least one of sodium dihydrogen phosphate, sodium pyrophosphate, sodium metaphosphate, tetraethyl orthosilicate, triethyl phosphite, triphenyl phosphite, diisooctyl phosphate, and alkyl phosphates.
[0047] In some typical implementations, transesterification inhibitors include sodium dihydrogen phosphate.
[0048] As mentioned above, the PC / PCTG alloy prepared from the raw materials provided in this application can combine high transparency, high and low temperature impact resistance, high flowability, and chemical resistance, making it suitable for a wide range of applications.
[0049] Accordingly, the present invention also provides a method for preparing the above-mentioned low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, comprising the following steps: extruding, cooling, granulating, drying, and injection molding the prepared raw materials after mixing according to the specified ratio.
[0050] Preferably, the extrusion is performed using a twin-screw extruder with a length-to-diameter ratio (L / D) of 32 to 44:1. The twin-screw extruder has 10 temperature zones, with the temperatures of the 10 zones being 100℃ to 120℃, 220℃ to 230℃, 230℃ to 230℃, 230℃ to 240℃, 230℃ to 240℃, 230℃ to 240℃, 230℃ to 240℃, and 230℃ to 240℃. The rotational speed of the twin-screw extruder is 200 rpm to 300 rpm.
[0051] In some typical implementations, the temperatures of the 10 temperature zones of the twin-screw extruder are 120°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, and 240°C, respectively, and the rotational speed of the twin-screw extruder is 240 rpm.
[0052] It should be noted that the preparation processes not described in detail above can be referred to relevant existing technologies, and will not be elaborated or limited here.
[0053] Furthermore, this invention also provides applications of the aforementioned low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy. For example, it can be used not only in the glass assembly industry, power tools, cleaning appliances, automotive industry, electronics, mechanical parts, optical discs, packaging, office equipment such as computers, medical and healthcare, films, leisure and protective equipment, etc., but also in environments requiring chemical resistance, transparency, a certain degree of drop resistance, and certain heat resistance, such as in household appliances such as robot vacuum cleaners.
[0054] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0055] Example 1
[0056] This embodiment provides a high-impact, transparent, and chemically resistant PC / PCTG alloy material. By mass percentage, its preparation raw materials include 27% bisphenol A type PC resin, 16% silicone copolymer PC resin, 54% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor. At this point, the mass ratio of bisphenol A type PC resin to PCTG resin is 1:2.
[0057] The bisphenol A type PC resin is a transparent bisphenol A type polycarbonate with a light transmittance of 89%; the silicone copolymer PC resin is a silicone copolymer PC resin with 6% siloxane; the toughening agent is methyl methacrylate-styrene-organosilicon-butyl acrylate; the antioxidant is composed of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and bis(2,4-dicumylphenyl)pentaerythritol diphosphite in a mass ratio of 1:1; the lubricant is PETS; and the transesterification inhibitor is sodium dihydrogen phosphate.
[0058] The preparation of this PC / PCTG alloy material includes: mixing the various raw materials in a high-speed mixer according to the specified ratio, and then feeding the mixture into a twin-screw extruder according to... Figure 1 The extrusion is performed using a combination of screws, followed by water-cooled granulation, drying, and injection molding. The temperatures of the 10 zones of the twin-screw extruder are set to 120℃, 230℃, 230℃, 230℃, 230℃, 230℃, 230℃, 230℃, and 240℃, respectively, and the main extruder speed is 240 rpm.
[0059] Example 2
[0060] The difference between this embodiment and Embodiment 1 is that the toughening agent is methyl methacrylate-butadiene styrene copolymer.
[0061] Example 3
[0062] The difference between this embodiment and Embodiment 1 is that the toughening agent is butadiene-styrene copolymer.
[0063] Example 4
[0064] The difference between this embodiment and Embodiment 1 is that the toughening agent is a methyl methacrylate-butadiene-styrene copolymer and an ethylene-methyl acrylate-glycidyl methacrylate terpolymer with a mass ratio of 1:1.
[0065] Example 5
[0066] The difference between this embodiment and Embodiment 1 is that the toughening agent is a 2:1 methyl methacrylate-butadiene-styrene copolymer and an ethylene-methyl acrylate-glycidyl methacrylate terpolymer.
[0067] Example 6
[0068] The difference between this embodiment and Embodiment 1 is that the toughening agent is a 1:2 methyl methacrylate-butadiene-styrene copolymer and an ethylene-methyl acrylate-glycidyl methacrylate terpolymer.
[0069] Example 7
[0070] The difference between this embodiment and Example 4 is that the raw materials include 25% bisphenol A type PC resin, 20% silicone copolymer PC resin with 6% siloxane content, 52.7% PCTG resin, 1.5% toughening agent, 0.4% antioxidant, 0.2% lubricant, and 0.2% transesterification inhibitor.
[0071] Example 8
[0072] The difference between this embodiment and Example 4 is that the raw materials include 20% bisphenol A type PC resin, 25% silicone copolymer PC resin with 6% siloxane content, 52.7% PCTG resin, 1.5% toughening agent, 0.4% antioxidant, 0.2% lubricant, and 0.2% transesterification inhibitor.
[0073] Example 9
[0074] The difference between this embodiment and embodiment 4 is that the 6% siloxane content of the silicone copolymer PC is replaced with the 8% siloxane content of the silicone copolymer PC resin.
[0075] Example 10
[0076] The difference between this embodiment and Embodiment 4 is that the silicone copolymer PC with a siloxane content of 6% is replaced with silicone copolymer PC resin with a siloxane content of 20%.
[0077] Comparative Example 1
[0078] This comparative example is essentially the same as Example 1, except that the silicone copolymer PC resin used in Example 1 is omitted, and it is replaced with bisphenol A type PC resin. Specifically, in this comparative example, the raw materials, by mass percentage, include 43% bisphenol A type PC resin, 54% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor. The mass ratio of bisphenol A type PC resin to PCTG resin is 1:1.26, and the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin is 1:0.
[0079] Comparative Example 2
[0080] This comparative example is essentially the same as Example 1, except that the bisphenol A type PC resin used in Example 1 is omitted, and it is replaced with silicone copolymer PC resin. Specifically, in this comparative example, the raw materials, by mass percentage, include 43% silicone copolymer PC resin, 54% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor.
[0081] Comparative Example 3
[0082] This comparative example is basically the same as Example 1, except that, in this comparative example, the raw materials, by mass, include 17% bisphenol A type PC resin, 20% silicone copolymer PC resin, 60% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor. At this time, the mass ratio of bisphenol A type PC resin to PCTG resin is 1:3.76, and the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin is 1:1.17.
[0083] Comparative Example 4
[0084] This comparative example is basically the same as Example 1, except that, in this comparative example, the raw materials, by mass percentage, include 17% bisphenol A type PC resin, 26% silicone copolymer PC resin, 54% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor. At this time, the mass ratio of bisphenol A type PC resin to PCTG resin is 1:3.17, and the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin is 1:5.3.
[0085] Comparative Example 5
[0086] This comparative example is basically the same as Example 1, except that, in this comparative example, the raw materials, by mass percentage, include 31% bisphenol A type PC resin, 12% silicone copolymer PC resin, 54% PCTG resin, 2% toughening agent, 0.4% antioxidant, 0.3% lubricant, and 0.3% transesterification inhibitor. At this time, the mass ratio of bisphenol A type PC resin to PCTG resin is 1:1.74, and the mass ratio of bisphenol A type PC resin to silicone copolymer PC resin is 1:0.39.
[0087] Comparative Example 6
[0088] The difference between this comparative example and Example 1 is that, by mass, the raw materials used in its preparation include: 99.4 parts of bisphenol A type PC resin, 0.4 parts of antioxidant, and 0.2 parts of lubricant.
[0089] The PC resin is a transparent bisphenol A type polycarbonate with a light transmittance of 89%. The antioxidant is composed of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] and bis(2,4-dicumylphenyl)pentaerythritol diphosphite in a mass ratio of 1:1. The lubricant is PETS.
[0090] Comparative Example 7
[0091] The difference between this comparative example and Example 1 is that, by mass, the raw materials used in its preparation include: 99.4% of PC resin with a 6% siloxane content, 0.4 parts of antioxidant, and 0.2 parts of lubricant.
[0092] The silicone copolymer PC resin is a copolymer PC resin with a siloxane content of 6%, the antioxidant is composed of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] and bis(2,4-dicumylphenyl)pentaerythritol-diphosphite in a mass ratio of 1:1, and the lubricant is PETS.
[0093] Comparative Example 8
[0094] The difference between this comparative example and Example 1 is that, by mass, the raw materials used in its preparation include: 99.4% of PC resin with 8% siloxane content, 0.4 parts of antioxidant, and 0.2 parts of lubricant.
[0095] The silicone copolymer PC resin is a copolymer PC resin with a siloxane content of 8%. The antioxidant consists of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and bis(2,4-dicumylphenyl)pentaerythritol diphosphite in a mass ratio of 1:1. The lubricant is PETS.
[0096] Comparative Example 9
[0097] The difference between this comparative example and Example 1 is that, by mass, the raw materials used in its preparation include: 99.4% PCTG resin, 0.4 parts antioxidant, and 0.2 parts lubricant.
[0098] The PCTG resin is a polyethylene terephthalate-1,4-cyclohexanediol resin with a viscosity of 1.00–1.05 L / g. The antioxidant consists of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] and bis(2,4-dicumylphenyl)pentaerythritol diphosphite in a 1:1 mass ratio. The lubricant is PETS.
[0099] Comparative Example 10
[0100] The difference between this comparative example and Example 1 is that the toughening agent of Example 1 is omitted in this comparative example. The raw materials for its preparation include, by mass parts: 27% bisphenol A type PC resin, 16% silicone copolymer PC resin with 6% siloxane content, 56% PCTG resin, 0.4% antioxidant, 0.3% lubricant and 0.3% transesterification inhibitor.
[0101] Comparative Example 11
[0102] The difference between this comparative example and Example 4 is that the transesterification inhibitor is zinc dihydrogen phosphate.
[0103] Comparative Example 12
[0104] The difference between this comparative example and Example 4 lies in the screw assembly of the extruder (the screw assembly is as follows). Figure 2 (As shown).
[0105] Comparative Example 13
[0106] The difference between this comparative example and Example 4 lies in the screw assembly of the extruder (the screw assembly is as follows). Figure 3 (As shown).
[0107] Test case
[0108] The materials prepared in Examples 1-10 and Comparative Examples 1-13 were subjected to the following performance tests, and the results are shown in Table 1.
[0109] The chemical corrosion resistance test conditions were based on ASTM D543: temperature 23℃±3℃; relative humidity ≤50%±10%; air pressure within the normal atmospheric pressure range; reagents such as floor cleaner, alcohol, Blue Moon laundry detergent, Mr. Muscle, and 84 disinfectant were applied to the sample strip respectively, the sample strip was kept bent using a stress test fixture, placed for 7 days, and then placed at room temperature for 2 hours to recover before checking the appearance of the sample.
[0110] Light transmittance was measured using a light transmittance tester; haze was measured using a light transmittance tester according to ASTM D1003; performance tests were conducted on Examples 1-11 and Comparative Examples 1-13 according to ISO standards. Among the various indicators, the -30℃ notched impact strength characterizes the low-temperature toughness of the material, haze represents the transparency of the standard material, heat distortion temperature characterizes the heat resistance temperature of the material, and melt flow index characterizes the processing fluidity of the material.
[0111] Table 1 Test Results
[0112]
[0113]
[0114] As can be seen from the table above, the low-temperature resistant, transparent, and chemically resistant PC / PCTG alloy materials provided in Examples 1-13 of this invention, compared with ordinary PC, have higher fluidity and excellent chemical resistance without affecting light transmittance and increasing low-temperature impact resistance.
[0115] As can be seen from Examples 1-6, the choice of toughening agent has a certain impact on the performance parameters of the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy material. Considering all parameters, Example 4 is the optimal example in this invention, exhibiting excellent heat distortion temperature, 2mm transmittance, and 2mm haze. The methyl methacrylate-butadiene-styrene copolymer selected in Example 4 is a transparent toughening agent with a refractive index close to that of PC and PCTG, thus not affecting the transparency of the PC / PCTG alloy. A large difference in refractive index would lead to light scattering and affect transparency. Furthermore, the methyl methacrylate-butadiene-styrene copolymer has a small particle size, resulting in a more uniform distribution in the system and improving the impact strength. The ethylene-methyl acrylate-glycidyl methacrylate selected in this scheme has high reactivity, further increasing the compatibility of PC and PCTG and further improving the impact strength. The combined use of these two agents results in the alloy product corresponding to Example 4 having the best overall performance, possessing high transparency, high impact resistance, heat resistance, and chemical resistance. Examples 7 and 8, while adjusting the weight percentage of the raw materials within the scope of this application, still exhibit good overall performance. Examples 9 and 10, by adjusting the siloxane content of the silicone copolymer PC resin, show that when the siloxane content is too high, the haze index increases significantly, while the transmittance and melt index decrease significantly. However, the low-temperature impact strength increases, but the material cost also increases. Based on comprehensive considerations, a siloxane content of 6%-8% yields the best results in this invention.
[0116] In Comparative Example 1, the silicone copolymer PC resin was omitted, resulting in poor performance of the material under low-temperature notched impact. In Comparative Example 2, the bisphenol A type PC resin was omitted, resulting in poor transparency at 2mm transmittance and 2mm haze. Furthermore, since all samples used silicone copolymer PC, the manufacturing cost of the material was high, making it unsuitable for commercialization. In Comparative Example 3, the mass ratios of bisphenol A type PC resin and PCTG resin were adjusted, resulting in a mass ratio outside the range specified in this application. This led to a decrease in the overall performance of the materials, failing to meet market application requirements. Similarly, in Comparative Example 4, the mass ratios of bisphenol A type PC resin, silicone copolymer PC resin, and PCTG resin were adjusted, resulting in both the mass ratios of bisphenol A type PC resin and PCTG resin, and the mass ratio of bisphenol A type PC resin and silicone copolymer PC resin, being outside the range specified in this application. This again resulted in a decrease in the overall performance of the materials, failing to meet market application requirements. In Comparative Example 5, the mass ratios of bisphenol A type PC resin and silicone copolymer PC resin were adjusted, resulting in a mass ratio outside the range specified in this application. This again resulted in a decrease in the overall performance of the materials, failing to meet commercialization requirements. As can be seen from Comparative Examples 3-5, excessively high silicone copolymer PC content leads to reduced system transparency; excessively high bisphenol A type PC content results in insufficient chemical resistance; and excessively high PCTG content leads to reduced heat resistance of the alloy material.
[0117] Comparative Examples 6-8 represent ordinary PC materials, and Comparative Example 9 represents PCTG resin. It can be seen that the individual resin materials cannot meet the overall performance requirements, lacking the combined properties of high transparency, high impact resistance, heat resistance, chemical resistance, and processability. Comparative Example 10 omitted the toughening agent, resulting in a significant decrease in the notched impact resistance of the material. Comparative Example 11 adjusted the transesterification inhibitor; in this case, microcracks appeared in the solvent resistance test.
[0118] Comparative Examples 12-13 and Example 4 show different screw combinations used, from Figures 1-3 It can be seen that the embodiments of this application use a screw combination with weaker shear, while Comparative Examples 12-13 use a screw combination with stronger shear. When a stronger screw combination is used, the dispersibility of the material is increased. It can be seen from the results of Comparative Examples 12-13 that the stronger screw causes a certain degree of degradation to the material, resulting in a decrease in the material's performance.
[0119] In summary, the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy provided by this invention uses bisphenol A type PC resin and silicone copolymer PC resin as the PC resin. The siloxane segments impart high flexibility to the material, absorbing energy through a microphase separation structure upon impact, significantly improving low-temperature impact resistance (maintaining toughness even below -30℃), thus avoiding the low-temperature brittleness problem of traditional PC. By adjusting the combination and ratio of raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy, it is beneficial to prepare PC / PCTG alloy products with high transparency, high impact resistance, high flowability, and chemical resistance. These products can be used not only in the glass assembly industry, power tools, cleaning appliances, automotive industry, electronics, mechanical parts, optical discs, packaging, office equipment such as computers, medical and healthcare products, films, leisure and protective equipment, but also in environments requiring chemical resistance, transparency, a certain degree of drop resistance, and certain heat resistance, such as in applications like robotic vacuum cleaners, steam mops, floor scrubbers, and power tool housings.
[0120] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy, characterized in that, By weight percentage, the raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy include: 10-30% bisphenol A type PC resin, 16-30% silicone copolymer PC resin, 36-65% PCTG resin, 1-3% toughening agent, 0.3-0.5% antioxidant, 0.2-0.5% lubricant, and 0.1-0.5% transesterification inhibitor; The mass ratio of the bisphenol A type PC resin to the PCTG resin is 1:1.35-2; the mass ratio of the bisphenol A type PC resin to the silicone copolymer PC resin is 1:0.59-1.25; and the silicone copolymer PC resin has a siloxane content of at least one of 6%, 8%, and 20%.
2. The low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy according to claim 1, characterized in that, The bisphenol A type PC resin is a transparent bisphenol A type polycarbonate with a light transmittance of ≥89%.
3. The low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy according to claim 1, characterized in that, By weight percentage, the raw materials for preparing the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy include: 20-27% bisphenol A type PC resin, 16-25% silicon copolymer PC resin, 36-65% PCTG resin, 1-2% toughening agent, 0.3-0.4% antioxidant, 0.2-0.4% lubricant, and 0.2-0.4% transesterification inhibitor.
4. The low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy according to claim 1, characterized in that, The PCTG resin is a polyethylene terephthalate-1,4-cyclohexanediol resin with a viscosity of 1.00~1.05 L / g. And / or, the toughening agent comprises at least one of methyl methacrylate-butadiene-styrene copolymer, ethylene-methyl methacrylate-glycidyl methacrylate terpolymer, butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer, ethylene-butyl methacrylate-glycidyl methacrylate copolymer, and methyl methacrylate-styrene-silicone-butyl acrylate. And / or, the antioxidant comprises at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide), tris[2,4-di-tert-butylphenyl] phosphite, oxaloyl(diimino-2,1-ethylidene)propionate (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and bis(2,4-dicumylphenyl)pentaerythritol diphosphite; And / or, the lubricant includes at least one of polyethylene wax, OP wax, PETS and montana wax; And / or, the transesterification inhibitor includes at least one of sodium dihydrogen phosphate, zinc dihydrogen phosphate, sodium pyrophosphate, sodium metaphosphate, tetraethyl orthosilicate, triethyl phosphite, triphenyl phosphite, diisooctyl phosphate, and alkyl phosphates.
5. A method for preparing a low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy, characterized in that, It includes extruding, cooling, granulating, drying, and injection molding the raw material for preparing the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy as described in any one of claims 1-4.
6. The method for preparing the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy according to claim 5, characterized in that, The extrusion is performed using a twin-screw extruder with a length-to-diameter ratio (L / D) of 32 to 44:
1.
7. The method for preparing the low-temperature impact-resistant, transparent, and chemically resistant PC / PCTG alloy according to claim 6, characterized in that, The twin-screw extruder has 10 temperature zones, with temperatures ranging from 100℃ to 120℃, 220℃ to 230℃, 230℃ to 230℃, 230℃ to 240℃, 230℃ to 240℃, 230℃ to 240℃, 230℃ to 240℃, 230℃ to 240℃, and 230℃ to 240℃. The rotational speed of the twin-screw extruder is 200 rpm to 300 rpm.
8. The application of the low-temperature impact-resistant, transparent, and chemical-resistant PC / PCTG alloy as described in any one of claims 1-4 in the manufacture of office equipment, medical devices, health care equipment, protective equipment, or household appliances.
Citation Information
Patent Citations
Transparent flame-retardant PC composite material and preparation method thereof
CN105924922A
Transparent PC composite and preparation method thereof
CN106009582A